Successful Photorefractive Keratectomy in a Case of Wilson's Disease. (25th August 2021) - Shokoohi-Rad, Saeed; Heidarzadeh, Hamid-Reza
Abstract : Purpose . To report a female with a history of Wilson's disease who underwent a successful photorefractive keratectomy (PRK) for myopic correction. Case Presentation . A twenty-year-old female with a history of Wilson's disease and D-penicillamine use was referred to our clinic for myopic refractive surgery. Her best-corrected visual acuity (BCVA) was 20/20 for both eyes with a refraction of ‐ 1.25 ‐ 0.5 ∗ 75 ° and ‐ 1.25 ‐ 0.25 ∗ 55 ° for the right and left eyes. The slit examination showed a prominent Kayser-Fleischer ring (K-F ring) in both eyes. She underwent a successful myopic PRK surgery, and her BCVA became 20/20 with no significant refraction. Conclusions . In this report, we report a successful PRK surgery for myopic correction in a case of Wilson's disease with prominent K-F rings in both eyes.